2017
DOI: 10.1038/s41598-017-17820-1
|View full text |Cite
|
Sign up to set email alerts
|

Direct Generation and Detection of Quantum Correlated Photons with 3.2 um Wavelength Spacing

Abstract: Quantum correlated, highly non-degenerate photons can be used to synthesize disparate quantum nodes and link quantum processing over incompatible wavelengths, thereby constructing heterogeneous quantum systems for otherwise unattainable superior performance. Existing techniques for correlated photons have been concentrated in the visible and near-IR domains, with the photon pairs residing within one micron. Here, we demonstrate direct generation and detection of high-purity photon pairs at room temperature wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 51 publications
(57 reference statements)
0
21
0
Order By: Relevance
“…To do this we note that the repetition period of our pump laser is 12.5 ns. Moreover, since the photon-pair generation process is spontaneous, there are no statistical correlations between subsequently emitted pairs as has been verified in [32,33]. Hence, the coincidence detection probability P 12 (0; 12.5 ns) equals the product of the probabilities for individual detections of two uncorrelated photons (i.e., photons from independent pairs emitted 12.5 ns apart): P(0; 12.5 ns) = P 1 (0)P 2 (12.5 ns).…”
Section: Acquisition Of Correlationsmentioning
confidence: 82%
“…To do this we note that the repetition period of our pump laser is 12.5 ns. Moreover, since the photon-pair generation process is spontaneous, there are no statistical correlations between subsequently emitted pairs as has been verified in [32,33]. Hence, the coincidence detection probability P 12 (0; 12.5 ns) equals the product of the probabilities for individual detections of two uncorrelated photons (i.e., photons from independent pairs emitted 12.5 ns apart): P(0; 12.5 ns) = P 1 (0)P 2 (12.5 ns).…”
Section: Acquisition Of Correlationsmentioning
confidence: 82%
“…Typical nonlinear materials, such as LN and KTP, provide access to SPDC wavelengths from ultraviolet to near infrared. SPDC in bulk ppLN as well as ppLN waveguides have already been used to generate non‐degenerate wavelength combinations with the signal in the visible and the idler at 4–5 µm. However, significantly longer wavelengths cannot be achieved due to the limited transparency range of these materials.…”
Section: Quantum Imaging Device Developmentmentioning
confidence: 99%
“…It has been shown that despite probabilistic operation, PDC sources can produce highly pure single photons approaching on‐demand operation in multiplexed schemes . There has been a surge of interest in single photon sources from nonlinear parametric processes operated in wider spectral regions and in mid‐IR in particular . The applications for mid‐IR single photon sources primarily concern quantum sensing and metrology, stealth ranging and quantum LIDARs, quantum‐enhanced medical imaging, as well as for free‐space secure communication in the atmospheric window, in light of recent demonstration of entanglement distribution using satellite‐to‐ground downlinks …”
Section: Introductionmentioning
confidence: 99%